Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.31557/apjcp.2019.20.6.1909
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Breast Cancer Patients with Human T-Cell Lymphotropic Virus Type-1 Infection

Abstract: Background:Human T-cell lymphotropic virus type 1 (HTLV-1) is a retrovirus that causes adult T-cell leukemia/lymphoma (ATL), an aggressive form of T-cell malignancy. The relationship between HTLV-1 infection and cancer progression is controversial. HTLV-1 encodes oncogenic protein TAX1 and it is hypothesized that HTLV-1 infection is associated with breast cancer progression. In this study, we evaluated the relationship between HTLV-1 infection and clinicopathological factors in breast cancer patients. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…A recent case report by Dahy et al reported a newly diagnosed small-cell lung cancer patient with a history of HTLV-1-associated myelopathy (6). Hirata et al evaluated the clinicopathologic features of HTLV-1-positive patients with breast cancer and found that these patients were older; however, their survival was unrelated to the virus infection (7). Other studies in this context are case reports on the association of HTLV-1 with other carcinomas, and there are no considerable studies in this context.…”
Section: Discussionmentioning
confidence: 99%
“…A recent case report by Dahy et al reported a newly diagnosed small-cell lung cancer patient with a history of HTLV-1-associated myelopathy (6). Hirata et al evaluated the clinicopathologic features of HTLV-1-positive patients with breast cancer and found that these patients were older; however, their survival was unrelated to the virus infection (7). Other studies in this context are case reports on the association of HTLV-1 with other carcinomas, and there are no considerable studies in this context.…”
Section: Discussionmentioning
confidence: 99%
“…The virus has known oncogenic potential in specific cancers, including the cervix, liver, head and neck, some lymphomas, and breast cancer 65 . HTLV-1 is one of the viruses that encode oncogenic protein Tax1 Binding Protein 1 (TAX1) and help breast cancer progression 66 . TAX1 protein can inactivate the function of cellular TP53 and postpone the G1 cell cycle arrest required for repairing DNA in response to DNA damage 67 .…”
Section: Discussionmentioning
confidence: 99%
“…Hirata et al 21 evaluated clinical and pathological factors in breast cancer patients and their relationship with HTLV-1 infection. There was no clinical or pathological aspect in this cancer related to HTLV-1, including the disease-free time and total survival, unless the patients infected with HTLV-1 were older.…”
Section: Discussionmentioning
confidence: 99%